Histological evaluation of hair keratin based templates in mice - Lee, Brennan Kiah Hui (2017)
Histology is important in a wide array of fields, but especially essential in the biological and biomedical field of research. There are a variety of staining techniques associated with histology to study biological tissues such as immunoperoxidase staining. In this project, templates made by human hair keratin in mice were evaluated. Human hair keratin has great potential in biomedical applications such as wound healing, and they have been identified as a biomaterial with great prospect due to the advantages it brings like its abundance, environmental-friendliness, ability to be autologous, to name a few. Thus it is important to evaluate human hair keratin templates in animal studies so that it can take that next step to clinical trials. We utilize two popular histological techniques, Hematoxylin and eosin (H&E) staining and Immunoperoxidase staining, to evaluate and analyse the biocompatibility of the keratin templates in mice. 2 types of keratin formulated templates (gel and sponge) and a commercially ready collagen derived positive control were implanted into mice subcutaneously and harvested after weeks 2 and 4, then embedded into paraffin before this project began. They were then sectioned and placed onto glass sides for staining. H&E staining was primarily used to analyse their integration to the tissue, vascularization, and cell penetration. Various antibodies were used in immunoperoxidase staining to provide specific information. Anti-human hair cortex cytokeratin and anti-CD68 were utilized to evaluate degradation and inflammation respectively. Anti-fibronectin, anti-collagen I, and anti-collagen III were also used to evaluate ECM formation. Evaluation results revealed that the keratin gels, when compared with the commercial positive control, display slightly inferior biocompatibility. The keratin sponge, however, provided more positive results as it revealed comparable biocompatibility compared to the positive control. Even though the results were not overwhelming, they show that keratin does have potential in biomedical applications, but more extensive studies are required.